MENINJAU BUKTI ILMIAH KEKUATAN BESI MENURUT CARA PANDANG ILMU KIMIA DAN SAINS YANG BERKAITAN BESERTA BEBERAPA KONSEKUENSINYA SEBAGAIMANA DISEBUT DALAM AL QURAN QS. AL HADIID:25 - Dede Suhendar (JURNAL ISTEK, 2011)
Kauniyah verses of iron in the Qur'an Surah Al Hadiid, Verse 25, in particular, has not been widely studied in the perspective of chemistry, let the problems associated with its implementation according to what is listed in the verse. In this paper, we discussed about of “great strength of iron” in the verse from the viewpoint of modern chemistry supported with findings of iron in other scientific disciplines are closely related with, as in Geology, Physics, Biology and Materials Science. In this paper, we also discussed the meaning of the next sentence of the verse